Work fatigue and attention performance in remise and taxi drivers - López, Soledad Susana; Ledesma, Rubén Daniel; Introzzi, María Isabel; Montes, Silvana Andrea (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2021)
Fatigue is considered a risk factor in traffic accidents, particularly in the case of professional drivers. In this population, extended working hours constitute one of the main precursors of fatigue. The objective of this work was to study the subjective perception of fatigue and the attentional performance in taxi / remise drivers at the beginning and end of a work day. Professional drivers (n = 30) were compared with a group of workers from different sectors (n = 30), matched by gender and age. A Fatigue severity scale, an Analogue visual fatigue scale, and a Conjunctive visual search task were administered. Overall, professional drivers showed higher scores in the fatigue severity scale. With regard to the attentional task, the ANOVA showed that professional drivers were less accurate in their performance. The practical implications of these findings are discussed.